2015
DOI: 10.1007/s00784-015-1601-6
|View full text |Cite
|
Sign up to set email alerts
|

Cementoblastic lineage formation in the cross-talk between stem cells of human exfoliated deciduous teeth and epithelial rests of Malassez cells

Abstract: The cemento/osteoblastic differentiation capability of SHED possesses a therapeutic potential in endodontic and periodontal tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Considering that the cementoblastoma arises from the uncontrolled proliferation of the cementoid matrix by cementoblasts[ 16 ] and that these cells are not present in the middle and cervical portions of the root[ 17 ], in the second surgical approach, removal of the root was performed up to the middle third, thereby eliminating all the cellular cement that could have led to the origin of the second lesion. However, this procedure may not eliminate the possibility of the lesion recurrence since other ethological factors as the uncontrolled induction of the cementoblasts differentiation by the epithelial rests of Malassez cells can be the trigger of the cementoblastoma lesions[ 18 ]. After one year of follow-up of this surgical procedure, repair with bone neoformation was verified in the region of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the cementoblastoma arises from the uncontrolled proliferation of the cementoid matrix by cementoblasts[ 16 ] and that these cells are not present in the middle and cervical portions of the root[ 17 ], in the second surgical approach, removal of the root was performed up to the middle third, thereby eliminating all the cellular cement that could have led to the origin of the second lesion. However, this procedure may not eliminate the possibility of the lesion recurrence since other ethological factors as the uncontrolled induction of the cementoblasts differentiation by the epithelial rests of Malassez cells can be the trigger of the cementoblastoma lesions[ 18 ]. After one year of follow-up of this surgical procedure, repair with bone neoformation was verified in the region of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The coculture systems were established through 6-well plate and 3 ÎŒm pore size transwell inserts (Corning) 21 . The hDPSCs were seeded in 6-well plate at the amount of 5×10 ^4 cells/well and the same quantity of hUCMSCs were seeded in the transwell inserts located in neighboring wells.…”
Section: Methodsmentioning
confidence: 99%
“…For example, UCMSCs could inhibit growth and promote apoptosis of HepG2 hepatocellular carcinoma cells 15 ; the viability and the secretion function were significantly increased in damaged mouse hepatocytes when they were indirect cocultured with UCMSCs 16 ; UCMSCs could efficiently suppress the proliferation and cytotoxicity of T cells and B cells in vitro 17 , 18 . As to DPSCs, some researches proved that they could affect biological characters of lymphocytes 19 , 20 and Malassez cells 21 in coculture condition. In recent years, a few scholars found that the paracrine effects also existed among different kinds of stem cells, which meant that the proliferation or differentiation abilities of stem cells could be modified by other kinds of stem cells 22 - 26 .…”
Section: Introductionmentioning
confidence: 99%
“…17 TGF-ÎČ1 signalling from HERS is responsible for inducing cementoblast differentiation. 18 Some authors have postulated a different origin of cementoblasts where HERS cells themselves undergo epithelial-ectomesenchymal transformation and directly differentiate into cementoblasts. 9,16,19 TGF-ÎČ1 and FGF2 have been proposed as factors stimulating this epithelial-ectomesenchymal transformation of HERS cells through a MAPK/ERK-dependent signalling pathway.…”
Section: Review Of Tooth Root Developmentmentioning
confidence: 99%